De-privatization in Higher Education: A Conceptual Approach - Kwiek, Marek (My University, 2017)
This paper seeks to conceptualize the processes of de-privatization in higher education. Trends of de-privatization (and contraction in enrolments) are highly interesting because they go against global trends of privatization (and educational expansion). Deprivatization means a decreasing role for the private component in the changing public–private dynamics. The paper studies its two dimensions (funding and provision) and distinguishes between seven potential empirical organizational/geographical levels of analysis. Empirically, the paper draws from data from Central Europe. The traditional dichotomous pairing of the public and the private is shown to still be useful in specific empirical contexts, despite it becoming blurred globally. Major approaches to privatization in higher education over the last two decades are rethought and redirected toward deprivatization. An empirically informed notion of de-privatization is being developed and its usefulness is briefly tested.
Keywords: De-privatization; Educational expansion; Educational contraction; Privatization; Public funding; Public–private dynamics; private higher education; Internal and external privatization; internal privatization; declining systems; declining student numbers; re-nationalization; Poland; private sector; Central Europe; private education providers; public and private provision